Digital Inclusion Strategies to Enhance Accessibility of Public Services in Indonesia - Ifa Shahrash; Risalatu Mirajiah; Nugroho Widyanto (Jurnal Aktor, 2022)
This article explores the strategies of digital inclusion in improving the accessibility of public services. With the increasing digitization of services, ensuring equitable access to public services for all citizens is crucial. The study examines the challenges faced in accessing public services, explores the concept of digital inclusion, and highlights strategies to enhance accessibility. The research utilizes a mixed-method approach, combining qualitative interviews and quantitative data analysis. The findings emphasize the importance of bridging the digital divide, promoting digital literacy, and creating user-centric digital platforms to enhance accessibility and inclusivity of public services. The article contributes to the discourse on digital inclusion and provides recommendations for policymakers and stakeholders to foster accessible and inclusive public service delivery.